Cave, Tree, Fountain. Language and Human Body Needs in Adam Smith’s Thought - López Lloret, Jorge (Analysis. Journal of Philosophical Research, 2020)
Between 1748 and 1764 Adam Smith defined a global and coherent philosophical project that he failed to publish in its entirety. The Theory of Moral Sentiments and The Wealth of Nations should be interpreted as parts of it that did come to be published. The present article presents as core elements of this project the Smithian theory of the origin of language and his vision of the human body as constitutively weak and sophisticated. Both are at the base of the historical process of socialization that, according to Smith, was together semiotic and economic in a non-problematic way. Finally, it reflects on the interest of this for the interpretation of Smith as an egalitarian no so focused on the marked and, from here, for our vision of ourselves as deficient beings that should expand their social ties as much as possible, because we need each other.